A fast-curing specimen sealing adhesive and preparation method thereof
By using a fast-curing specimen sealant composed of mixed phenol epoxy ethylene resin, triethylene glycol dimethacrylate and photoinitiator, the problems of strong xylene volatility and long curing time in traditional sealant methods are solved, and a more efficient and safe pathological section sealant process is achieved.
Patent Information
- Application Number
- CN202411451649.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-10-17
AI Technical Summary
Traditional pathological section sealing methods have problems such as strong volatility of xylene, resulting in environmental pollution, and long curing time to affect diagnostic efficiency.
The fast curing specimen sealant consisting of mixed phenol epoxy ethylene resin, triethylene glycol dimethacrylate and photoinitiator (such as camphorquinone) was used to achieve rapid curing by 5 seconds of ultraviolet light.
It significantly shortens curing time, reduces the emanation of xylene, improves diagnostic efficiency, improves laboratory environment, and provides safer operating conditions.
Smart Images

Figure BDA0005089311180000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of curing glue, and in particular to a fast-curing specimen sealing glue and a preparation method thereof. Background Art
[0002] In the field of pathology, pathological section examination is one of the important means of diagnosing diseases. Through microscopic observation of tissue samples, pathologists can identify morphological changes in cells and thus determine the nature and progression of the disease. During surgery, especially in surgery involving tumors, rapid and accurate pathological diagnosis is essential for deciding the surgical plan. However, there are some limitations in the traditional pathological section preparation process, especially in the sealing process, which has a significant impact on diagnostic efficiency. In pathological section examination, the main purpose of sealing is to protect the specimen from contamination and physical damage. Usually, after the pathological section is prepared, a few drops of sealing glue need to be added to the specimen to ensure the integrity and stability of the specimen. However, there are several major problems with the traditional sealing method.
[0003] During the sealing process, the specimen must be sealed before xylene dries. Xylene (chemical formula: C8H10) is a commonly used organic solvent with a strong odor and is recognized by the World Health Organization as a Class III carcinogen. It is highly volatile and will be emitted in large quantities during the sealing process, causing the laboratory environment to be filled with unpleasant and toxic gases. This not only poses a threat to the health of medical workers, but may also cause discomfort to patients and their families.
[0004] The traditional sealing method requires the specimen to dry for more than four hours before the coverslip can be applied. This long waiting time is unacceptable in clinical practice, especially during surgery, when doctors need to quickly obtain pathological results to decide on surgical plans. For patients and their families, this waiting time is difficult and anxious.
[0005] In summary, the development and application of fast-curing specimen sealing technology will bring revolutionary changes to pathological diagnosis, significantly improve diagnostic efficiency, improve the laboratory environment, and provide patients and medical workers with a safer operating experience. Summary of the invention
[0006] In view of this, the purpose of the present invention is to propose a fast-curing specimen sealant and a preparation method thereof, so as to shorten the curing time, reduce the emission of xylene, win precious life time for patients, shorten the operation time for medical workers, and liberate medical workers from the harsh environment of xylene.
[0007] Based on the above purpose, the present invention provides a fast-curing specimen sealant, which is obtained by mixing the following raw materials in parts by weight: 3-4 parts of mixed phenol epoxy vinyl resin, 0.8-1.5 parts of triethylene glycol dimethacrylate and 0.1-0.5 parts of photoinitiator.
[0008] Preferably, the photoinitiator is camphorquinone.
[0009] Furthermore, the preparation method of the mixed phenol epoxy vinyl resin is as follows:
[0010] (1) bisphenol F, 4,4'-dihydroxybiphenyl, 4,4,4-trihydroxytrimethylbenzene, epichlorohydrin and trimethylbenzyl ammonium chloride are mixed, stirred at room temperature for 5-20 minutes, heated to 90-100° C., stirred for 10-14 hours, cooled to 25-35° C., and sodium hydroxide aqueous solution is added dropwise. After the addition is complete, the mixture is stirred for 10-14 hours, and purified to obtain a mixed phenol epoxy resin;
[0011] (2) adding a mixed phenol epoxy resin and hydroquinone to toluene, heating to 75-85° C., stirring for 20-40 min, and dropping a mixture of acrylic acid and N,N-dimethylbenzylamine. After the dropping is complete, heating to 100-110° C., stirring and reacting until the acid value of the system drops to 5 mgKOH / g, and purifying to obtain a mixed phenol epoxy vinyl resin;
[0012] Preferably, in step (1), the molar ratio of bisphenol F, 4,4'-dihydroxybiphenyl and 4,4,4-trihydroxytrimethylbenzene is 1:0.3-0.7:0.05-0.15;
[0013] Preferably, the amount of epichlorohydrin added in step (1) is 8-12 times the total molar amount of bisphenol F, 4,4'-dihydroxybiphenyl and 4,4,4-trihydroxytrimethylbenzene.
[0014] Preferably, the amount of trimethylbenzyl ammonium chloride added in step (1) is 1% to 2% of the total weight of bisphenol F, 4,4'-dihydroxybiphenyl and 4,4,4-trihydroxytrimethylbenzene.
[0015] Preferably, the amount of sodium hydroxide added in step (1) is 1.5-2.5 times the total molar amount of bisphenol F, 4,4'-dihydroxybiphenyl and 4,4,4-trihydroxytrimethylbenzene.
[0016] Preferably, the concentration of the sodium hydroxide aqueous solution in step (1) is 35 wt %.
[0017] Preferably, the amount of hydroquinone added in step (2) is 1%-2% of the total weight of the mixed phenol epoxy resin and acrylic acid.
[0018] Preferably, in step (2), the weight ratio of the mixed phenol epoxy resin to acrylic acid is 3:2.5-3.
[0019] Preferably, the amount of toluene added in step (2) is 4-6 times the weight of the mixed phenol epoxy resin.
[0020] Preferably, the amount of N,N-dimethylbenzylamine added in step (2) is 1%-3% by weight of acrylic acid.
[0021] Furthermore, the present invention also provides a method for preparing a fast-curing specimen sealing adhesive, comprising the following steps: mixing mixed phenol epoxy vinyl resin, triethylene glycol dimethacrylate and camphorquinone, and stirring for 20-40 minutes to obtain a fast-curing specimen sealing adhesive.
[0022] Beneficial effects of the present invention:
[0023] The fast-curing specimen sealant prepared by the present invention exhibits excellent performance in many aspects. After 5 seconds of ultraviolet light irradiation, it exhibits high hardness and excellent adhesion, and its thermal decomposition temperature is relatively high, indicating outstanding heat resistance. The extremely low oxygen permeability not only protects pathological sections, but also effectively prevents the release of volatile toxic substances such as xylene; the extremely high light transmittance is conducive to detailed observation and detection. The specimen sealant provided by the present invention can replace both cover glass and sealant, providing an optional solution for pathologists and a reference basis for basic science.
[0024] The present invention significantly improves adhesion, light transmittance and gas barrier properties by using 4,4'-dihydroxybiphenyl. The introduction of 4,4,4-trihydroxytrimethylbenzene enhances hardness and gas barrier properties. When the two are used in combination, the synergistic effect significantly improves gas barrier properties, further regulates light transmittance, and achieves high hardness and high adhesion at the same time, which is mainly attributed to its intramolecular rotation and extramolecular cross-linking.
[0025] The triethylene glycol dimethacrylate used in the present invention has a relatively long flexible chain, which helps to provide significant adhesion and improve internal stress, reduce microscopic defects, and improve light transmittance and gas isolation performance. DETAILED DESCRIPTION
[0026] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0027] Example 1: (1) 2 g of bisphenol F, 0.93 g of 4,4'-dihydroxybiphenyl, 0.29 g of 4,4,4-trihydroxytrimethylbenzene, 15.28 g of epichlorohydrin and 0.05 g of trimethylbenzyl ammonium chloride were mixed, stirred at room temperature for 10 min, heated to 95° C., stirred for 12 h, cooled to 30° C., and 1.2 g of a 35 wt% aqueous sodium hydroxide solution was added dropwise. After the addition was completed, stirring was continued for 12 h, and the unreacted epichlorohydrin was removed by rotary evaporation. The mixture was repeatedly extracted with deionized water and dichloromethane, and the organic phase was taken, rotary evaporation was performed to remove dichloromethane, and vacuum drying was performed to obtain a mixed phenol epoxy resin;
[0028] (2) 3 g of mixed phenol epoxy resin and 0.1 g of hydroquinone were added to 15 g of toluene, the temperature was raised to 80° C., and the mixture was stirred for 30 min. A mixed solution of 2.7 g of acrylic acid and 0.05 g of N,N-dimethylbenzylamine was added dropwise. After the addition was completed, the temperature was raised to 105° C. and the mixture was stirred and reacted until the acid value of the system dropped to 5 mgKOH / g. The reaction was terminated, and the solvent and unreacted acrylic acid were removed by rotary evaporation to obtain a mixed phenol epoxy vinyl resin;
[0029] (3) 3.5 g of mixed phenol epoxy vinyl resin, 1.2 g of triethylene glycol dimethacrylate and 0.24 g of camphorquinone were mixed and stirred for 30 min to obtain a fast-curing specimen sealing adhesive.
[0030] Example 2: (1) 2 g of bisphenol F, 0.59 g of 4,4'-dihydroxybiphenyl, 0.15 g of 4,4,4-trihydroxytrimethylbenzene, 10.32 g of epichlorohydrin and 0.03 g of trimethylbenzyl ammonium chloride were mixed, stirred at room temperature for 5 min, heated to 90° C., stirred for 10 h, cooled to 25° C., and 0.76 g of a 35 wt% sodium hydroxide aqueous solution was added dropwise. After the addition was completed, stirring was continued for 10 h, and the unreacted epichlorohydrin was removed by rotary evaporation. The mixture was repeatedly extracted with deionized water and dichloromethane, and the organic phase was taken, rotary evaporation was performed to remove dichloromethane, and vacuum drying was performed to obtain a mixed phenol epoxy resin;
[0031] (2) adding 3 g of mixed phenol epoxy resin and 0.1 g of hydroquinone to 15 g of toluene, heating to 75° C., stirring for 20 min, and dropping a mixture of 2.5 g of acrylic acid and 0.03 g of N,N-dimethylbenzylamine. After the dropping is complete, heating to 100° C. and stirring to react until the acid value of the system drops to 5 mgKOH / g, terminating the reaction, and performing rotary evaporation to remove the solvent and unreacted acrylic acid to obtain a mixed phenol epoxy vinyl resin;
[0032] (3) 3 g of mixed phenol epoxy vinyl resin, 0.8 g of triethylene glycol dimethacrylate and 0.1 g of camphorquinone were mixed and stirred for 20 min to obtain a fast-curing specimen sealing adhesive.
[0033] Example 3: (1) 2 g of bisphenol F, 1.30 g of 4,4'-dihydroxybiphenyl, 0.43 g of 4,4,4-trihydroxytrimethylbenzene, 21.20 g of epichlorohydrin and 0.07 g of trimethylbenzyl ammonium chloride were mixed, stirred at room temperature for 20 min, heated to 100° C., stirred for 14 h, cooled to 35° C., and 1.73 g of a 35 wt % sodium hydroxide aqueous solution was added dropwise. After the addition was complete, stirring was continued for 14 h, and the unreacted epichlorohydrin was removed by rotary evaporation. The mixture was repeatedly extracted with deionized water and dichloromethane, and the organic phase was taken, rotary evaporation was performed to remove dichloromethane, and vacuum drying was performed to obtain a mixed phenol epoxy resin;
[0034] (2) 3 g of mixed phenol epoxy resin and 0.1 g of hydroquinone were added to 15 g of toluene, the temperature was raised to 80° C., and the mixture was stirred for 40 min. A mixed solution of 3 g of acrylic acid and 0.09 g of N,N-dimethylbenzylamine was added dropwise. After the addition was completed, the temperature was raised to 110° C. and the mixture was stirred and reacted until the acid value of the system dropped to 5 mgKOH / g. The reaction was terminated, and the solvent and unreacted acrylic acid were removed by rotary evaporation to obtain a mixed phenol epoxy vinyl resin;
[0035] (3) 4 g of mixed phenol epoxy vinyl resin, 1.5 g of triethylene glycol dimethacrylate and 0.5 g of camphorquinone were mixed and stirred for 40 min to obtain a fast-curing specimen sealing adhesive.
[0036] Comparative Example 1:
[0037] The difference between Comparative Example 1 and Example 1 is that: 4,4'-dihydroxybiphenyl is not added in step (1);
[0038] The specific steps are as follows:
[0039] (1) 3 g of bisphenol F, 0.29 g of 4,4,4-trihydroxytrimethylbenzene, 15.28 g of epichlorohydrin and 0.05 g of trimethylbenzyl ammonium chloride were mixed, stirred at room temperature for 10 min, heated to 95° C., stirred for 12 h, cooled to 30° C., and 1.2 g of a 35 wt % sodium hydroxide aqueous solution was added dropwise. After the addition was complete, stirring was continued for 12 h, and the unreacted epichlorohydrin was removed by rotary evaporation. The mixture was repeatedly extracted with deionized water and dichloromethane, and the organic phase was taken, rotary evaporation was performed to remove dichloromethane, and vacuum drying was performed to obtain a mixed phenol epoxy resin;
[0040] (2) 3 g of mixed phenol epoxy resin and 0.1 g of hydroquinone were added to 15 g of toluene, the temperature was raised to 80° C., and the mixture was stirred for 30 min. A mixed solution of 2.7 g of acrylic acid and 0.05 g of N,N-dimethylbenzylamine was added dropwise. After the addition was completed, the temperature was raised to 105° C. and the mixture was stirred and reacted until the acid value of the system dropped to 5 mgKOH / g. The reaction was terminated, and the solvent and unreacted acrylic acid were removed by rotary evaporation to obtain a mixed phenol epoxy vinyl resin;
[0041] (3) 3.5 g of mixed phenol epoxy vinyl resin, 1.2 g of triethylene glycol dimethacrylate and 0.24 g of camphorquinone were mixed and stirred for 30 min to obtain a specimen sealing glue.
[0042] Comparative Example 2:
[0043] The difference between Comparative Example 2 and Example 1 is that: 4,4,4-trihydroxytrimethylbenzene is not added in step (1);
[0044] The specific steps are as follows:
[0045] (1) 2.2 g of bisphenol F, 0.93 g of 4,4'-dihydroxybiphenyl, 15.28 g of epichlorohydrin and 0.05 g of trimethylbenzyl ammonium chloride were mixed, stirred at room temperature for 10 min, heated to 95° C., stirred for 12 h, cooled to 30° C., and 1.2 g of a 35 wt % sodium hydroxide aqueous solution was added dropwise. After the addition was completed, stirring was continued for 12 h, and unreacted epichlorohydrin was removed by rotary evaporation. The mixture was repeatedly extracted with deionized water and dichloromethane, and the organic phase was taken, rotary evaporation was performed to remove dichloromethane, and vacuum drying was performed to obtain a mixed phenol epoxy resin;
[0046] (2) 3 g of mixed phenol epoxy resin and 0.1 g of hydroquinone were added to 15 g of toluene, the temperature was raised to 80° C., and the mixture was stirred for 30 min. A mixed solution of 2.7 g of acrylic acid and 0.05 g of N,N-dimethylbenzylamine was added dropwise. After the addition was completed, the temperature was raised to 105° C. and the mixture was stirred and reacted until the acid value of the system dropped to 5 mgKOH / g. The reaction was terminated, and the solvent and unreacted acrylic acid were removed by rotary evaporation to obtain a mixed phenol epoxy vinyl resin;
[0047] (3) 3.5 g of mixed phenol epoxy vinyl resin, 1.2 g of triethylene glycol dimethacrylate and 0.24 g of camphorquinone were mixed and stirred for 30 min to obtain a specimen sealing glue.
[0048] Comparative Example 3:
[0049] The difference between Comparative Example 3 and Example 1 is that: in step (1), no 4,4'-dihydroxybiphenyl and 4,4,4-trihydroxytrimethylbenzene are added;
[0050] The specific steps are as follows:
[0051] (1) 3.2 g of bisphenol F, 15.28 g of epichlorohydrin and 0.05 g of trimethylbenzyl ammonium chloride were mixed, stirred at room temperature for 10 min, heated to 95° C., stirred for 12 h, cooled to 30° C., and 1.2 g of a 35 wt % sodium hydroxide aqueous solution was added dropwise. After the addition was complete, stirring was continued for 12 h, and the unreacted epichlorohydrin was removed by rotary evaporation. The unreacted epichlorohydrin was extracted repeatedly with deionized water and dichloromethane. The organic phase was taken, rotary evaporation was performed to remove dichloromethane, and vacuum drying was performed to obtain a bisphenol F epoxy resin;
[0052] (2) adding 3 g of bisphenol F epoxy resin and 0.1 g of hydroquinone to 15 g of toluene, heating to 80° C., stirring for 30 min, and dropping a mixture of 2.7 g of acrylic acid and 0.05 g of N,N-dimethylbenzylamine. After the dropping is complete, heating to 105° C., stirring and reacting until the acid value of the system drops to 5 mgKOH / g, terminating the reaction, and performing rotary evaporation to remove the solvent and unreacted acrylic acid to obtain bisphenol F epoxy vinyl resin;
[0053] (3) 3.5 g of bisphenol F epoxy vinyl resin, 1.2 g of triethylene glycol dimethacrylate and 0.24 g of camphorquinone were mixed and stirred for 30 min to obtain a specimen sealing glue.
[0054] Comparative Example 4:
[0055] The difference between Comparative Example 4 and Example 1 is that the triethylene glycol dimethacrylate in step (3) is replaced by an equal molar amount of ethylene glycol dimethacrylate;
[0056] The specific steps are as follows:
[0057] (1) 2 g of bisphenol F, 0.93 g of 4,4'-dihydroxybiphenyl, 0.29 g of 4,4,4-trihydroxytrimethylbenzene, 15.28 g of epichlorohydrin and 0.05 g of trimethylbenzyl ammonium chloride were mixed, stirred at room temperature for 10 min, heated to 95° C., stirred for 12 h, cooled to 30° C., and 1.2 g of a 35 wt % sodium hydroxide aqueous solution was added dropwise. After the addition was completed, stirring was continued for 12 h, and the unreacted epichlorohydrin was removed by rotary evaporation. The mixture was repeatedly extracted with deionized water and dichloromethane, and the organic phase was taken, rotary evaporation was performed to remove dichloromethane, and vacuum drying was performed to obtain a mixed phenol epoxy resin;
[0058] (2) 3 g of mixed phenol epoxy resin and 0.1 g of hydroquinone were added to 15 g of toluene, the temperature was raised to 80° C., and the mixture was stirred for 30 min. A mixed solution of 2.7 g of acrylic acid and 0.05 g of N,N-dimethylbenzylamine was added dropwise. After the addition was completed, the temperature was raised to 105° C. and the mixture was stirred and reacted until the acid value of the system dropped to 5 mgKOH / g. The reaction was terminated, and the solvent and unreacted acrylic acid were removed by rotary evaporation to obtain a mixed phenol epoxy vinyl resin;
[0059] (3) 3.5 g of mixed phenol epoxy vinyl resin, 0.83 g of ethylene glycol dimethacrylate and 0.24 g of camphorquinone were mixed and stirred for 30 min to obtain a specimen sealing glue.
[0060] Performance Test:
[0061] Preparation of cured samples: The specimen sealants prepared in the examples and comparative examples were coated on a glass slide, and then placed under an ultraviolet lamp with a wavelength of 405 nm, the power was adjusted to 260 W, and irradiated for 5 seconds to harden, thereby obtaining a cured sample.
[0062] Hardness test: According to the national standard "Coating Hardness Pencil Test Method", the cured samples were scratched in turn. For the cured samples with scratches, the hardness of the wooden pencil was recorded, and the marking operation was repeated once. The results are shown in Table 1.
[0063] Adhesion test: The cross-hatch method was used to test. A certain area was selected and the cured sample was evenly scratched with a cross-hatch tool to form 100 small grids in the area. The small grid area was adhered and pulled with raw tape, and the peeling condition was recorded. The adhesion level was determined based on the peeling condition. The results are shown in Table 1.
[0064] Thermal stability: The thermal decomposition temperature of the cured sample was measured using a thermal gravimetric analyzer (TGA). Test conditions: Under nitrogen atmosphere, the heating rate was 10°C / min, the flow rate of the protective gas was 20 ml / min, and the test temperature range was 50-700°C. The results are shown in Table 1.
[0065] Air permeability: The test was conducted using an air permeability meter in accordance with the national standard “Plastic Film and Sheet Gas Permeability Test Method - Pressure Difference Method”. The results are shown in Table 1.
[0066] Light transmittance: A UV-visible photometer was used with air as a control to measure the light transmittance at an incident wavelength of 550 nm. The results are shown in Table 1.
[0067] Table 1 Performance test results
[0068]
[0069] Data Analysis:
[0070] It can be seen from the data of Examples 1-3 in Table 1 that the fast-curing specimen sealant prepared by the present invention has a high hardness and excellent adhesion after being irradiated with ultraviolet light for 5 seconds. It also has a high thermal decomposition temperature, indicating that it has excellent heat resistance. Most importantly, it also has extremely low oxygen permeability and extremely high light transmittance. The extremely low oxygen permeability helps to protect pathological sections and prevent the volatilization of toxic substances such as xylene, while the extremely high light transmittance helps observation and detection.
[0071] It can be seen from the data of Example 1 and Comparative Example 1 in Table 1 that 4,4'-dihydroxybiphenyl helps to improve the adhesion, light transmittance and gas barrier properties of the sample after the specimen sealant is cured.
[0072] It can be seen from the data of Example 1 and Comparative Example 2 in Table 1 that 4,4,4-trihydroxytrimethylbenzene helps to improve the hardness and gas barrier properties of the sample after the specimen sealant is cured.
[0073] It can be seen from the data of Example 1 and Comparative Example 3 in Table 1 that 4,4'-dihydroxybiphenyl and 4,4,4-trihydroxytrimethylbenzene synergistically improve the gas barrier properties of the sample after the specimen sealant is cured, regulate the light transmittance, and achieve high hardness and high adhesion, which is mainly due to the intramolecular rotation and extramolecular cross-linking of 4,4'-dihydroxybiphenyl and 4,4,4-trihydroxytrimethylbenzene.
[0074] It can be seen from the data of Example 1 and Comparative Example 4 in Table 1 that triethylene glycol dimethacrylate can improve the adhesion, transmittance and gas barrier properties of the sample after the specimen sealant is cured. This may be because triethylene glycol dimethacrylate has a long flexible chain, which helps to relieve interfacial stress concentration, thereby improving adhesion, and can regulate internal stress and reduce microscopic defects, thereby improving transmittance and gas barrier properties.
[0075] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A fast-curing specimen sealant, characterized in that: The method is prepared by mixing the following raw materials, in parts by weight: 3-4 parts of mixed phenol epoxy vinyl resin, 0.8-1.5 parts of triethylene glycol dimethacrylate and 0.1-0.5 parts of photoinitiator; The preparation method of the mixed phenol epoxy vinyl resin is as follows: (1) bisphenol F, 4,4'-dihydroxybiphenyl, 4,4,4-trihydroxytrimethylbenzene, epichlorohydrin and trimethylbenzyl ammonium chloride are mixed, stirred at room temperature for 5-20 minutes, heated to 90-100° C., stirred for 10-14 hours, cooled to 25-35° C., and sodium hydroxide aqueous solution is added dropwise. After the addition is complete, the mixture is stirred for 10-14 hours, and purified to obtain a mixed phenol epoxy resin; (2) adding a mixed phenol epoxy resin and hydroquinone to toluene, heating to 75-85° C., stirring for 20-40 min, and dropping a mixture of acrylic acid and N,N-dimethylbenzylamine. After the dropping is complete, heating to 100-110° C., stirring and reacting until the acid value of the system drops to 5 mgKOH / g, and purifying to obtain a mixed phenol epoxy vinyl resin; In the step (1), the molar ratio of bisphenol F, 4,4'-dihydroxybiphenyl and 4,4,4-trihydroxytrimethylbenzene is 1:0.3-0.7:0.05-0.15; In the step (2), the weight ratio of the mixed phenol epoxy resin to acrylic acid is 3:2.5-3.
2. The fast-curing specimen sealant according to claim 1, characterized in that: In the step (1), the amount of epichlorohydrin added is 8-12 times the total molar amount of bisphenol F, 4,4'-dihydroxybiphenyl and 4,4,4-trihydroxytrimethylbenzene.
3. The fast-curing specimen sealant according to claim 1, characterized in that: In the step (1), the amount of trimethylbenzyl ammonium chloride added is 1% to 2% of the total weight of bisphenol F, 4,4'-dihydroxybiphenyl and 4,4,4-trihydroxytrimethylbenzene.
4. The fast-curing specimen sealant according to claim 1, characterized in that: In the step (1), the amount of sodium hydroxide added is 1.5-2.5 times the total molar amount of bisphenol F, 4,4'-dihydroxybiphenyl and 4,4,4-trihydroxytrimethylbenzene; and the concentration of the sodium hydroxide aqueous solution is 35wt%.
5. The fast-curing specimen sealant according to claim 1, characterized in that: The amount of hydroquinone added in step (2) is 1%-2% of the total weight of the mixed phenol epoxy resin and acrylic acid.
6. The fast-curing specimen sealant according to claim 1, characterized in that: The amount of toluene added in step (2) is 4-6 times the weight of the mixed phenol epoxy resin.
7. The fast-curing specimen sealant according to claim 1, characterized in that: In the step (2), the amount of N,N-dimethylbenzylamine added is 1%-3% of the weight of acrylic acid.
8. The fast-curing specimen sealant according to claim 1, characterized in that: The photoinitiator is camphorquinone.
9. A method for preparing a fast-curing specimen sealant according to any one of claims 1 to 8, characterized in that: The following steps are involved: Mix the mixed phenol epoxy vinyl resin, triethylene glycol dimethacrylate and camphorquinone, and stir for 20-40 minutes to obtain a fast-curing specimen sealing adhesive.
Citation Information
Patent Citations
Adhesive for replacing cover glass and preparation method and application of adhesive
CN113265216A
Preparation method and application of adhesive
CN115353835A